Validity and reliability of the Newtest Powertimer 300-series® testing system - Enoksen, E.; Tonnessen, E.; Shalfawi, S. (Journal of Sports Sciences, 2009)
The aim of the present study was to assess the reliability and validity of the Newtest Powertimer 300-series® portable contact mat and photocells (Newtest Oy, Finland). The participants were 20 male soccer players aged 19.1±3.5 years. The validity and reliability of the Powertimer (contact mat and photocells) were assessed in a comparison of a laboratory testing method (force platform and photocells) and the Newtest Powertimer system. All participants were tested on 40-m sprint, countermovement jump, and squat jump. The results showed that the Powertimer was a reliable instrument for both jumping and running. The system did not show any marked systematic bias (P < 0.05) and the random error associated with it was negligible. A comparison of the laboratory testing method with the Powertimer revealed that the Powertimer contact mat and photocells had poor validity and the bias in measurement differed from that of the laboratory testing method (P < 0.05). The Newtest Powertimer testing system was shown to be a useful instrument for measuring jump height and running speed. However, if a comparison of overall values of jumping height is intended, it is important to use the same testing system, because different systems give different results. It is also advisable to use this equipment only if no other "gold standard" equipment is available.